PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DALAM UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS XII MIPA 2 SMA NEGERI 1 PETANG TAHUN PELAJARAN 2019/2020 - I Made Arsana (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
The STAD learning model is an approach to encourage students to encourage and help each other, to master the skills taught by the teacher. This study aims to determine the improvement of students' mathematics learning outcomes with the application of the STAD type cooperative learning model. This type of research is Classroom Action Research which is designed with two cycles, each cycle consists of four stages, namely: planning, implementation, observation and reflection. The subjects of this study were students of class XII MIPA 2 SMA Negeri 1 Evening in the 2019/2020 academic year. The object of this research was the application of the STAD type cooperative learning model and student learning outcomes. The data collection methods used in this study were the test method, the observation method, and the documentation method. The results of the research in the first cycle, the number of students who completed the first cycle were 18 students and 12 students did not complete, with an average score of 73.67 student learning outcomes and 73.67% student absorption. In cycle II, the number of students who completed was 29 students with an average score of 81.17 student learning outcomes and 81.17% student absorption. The average increase in student learning outcomes is 7.50. The average percentage of activities increased by 11.88%, from 51.12% in the first cycle which was classified as quite active to 63% in the second cycle which was classified as active.